Development and validity of a mobile application prototype for hospital shift handover - Luciana Pizolio Garcia Dematte; André Estevam Jaques; Carla Moretti de Souza; Martina Mesquita Tonon; Cátia Millene Dell’Agnolo; Cremilde Aparecida Trindade Radovanovic; Adriane Bochi Cândido; Milton Alejandro Jorquera Malebrán (Revista Brasileira de Enfermagem)
ABSTRACT Objective: To develop and validate a mobile application prototype for nursing shift handover in a hospital inpatient unit. Methods: A methodological study of technological production, carried out from April 2020 to January 2022, for mobile application construction and validity through the Design Thinking methodology. The study involved the stages of prototype development and validity by experts. Results: The application for mobile nursing shift handover obtained a usability score of 79 points and a content validity coefficient of 0.7. Conclusions: The instrument obtained an excellent assessment according to usability and agreement among experts. However, future studies are needed to implement this technology in order to assess effectiveness, time optimization and failures during communication.